1999
DOI: 10.1159/000016531
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prevention in a Community–Dwelling Older Population

Abstract: A clinical trial was conducted to compare the effect of different caries–preventive strategies on caries progression in lower–income, ethnically diverse persons 60 years of age and older. Two hundred and ninety–seven subjects were randomized into one of five experimental groups. Group 1 received usual care from a public health department or a private practitioner. Group 2 received an educational program of 2 h duration implemented twice a year. Group 3 received the educational program plus a 0.12% chlorhexidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
0
21
0
1
Order By: Relevance
“…Analyses could not be performed for varnish containing 22,500 ppm F -(Duraphat), since these studies used Duraphat as a control group without having a second (negative) control group (Ravald and Birkhed 1992;Fure and Lingstrom 2009) or the results were presented according to different indices (DMFRS or texture) and did not report all information required for recalculation (Schaeken et al 1991;Tan et al 2010). For CHX mouth rinses (Powell et al 1999;Wyatt and MacEntee 2004;Wyatt et al 2007) and ozone treatment (Holmes 2003;Baysan and Lynch 2007), recalculation was not possible owing to insufficient data presentation. Thus, meta-analyses were performed only for dentifrice containing 5,000 ppm F -or 1.5% arginine plus 1,450 ppm F -, rinse containing 0.05% to 0.2% NaF (225 to 900 ppm F -), varnish containing SDF or CHX and combined use of dentifrice (1,500 ppm F -), and a rinse containing AmF/SnF 2 (250 ppm F -).…”
Section: Resultsmentioning
confidence: 99%
“…Analyses could not be performed for varnish containing 22,500 ppm F -(Duraphat), since these studies used Duraphat as a control group without having a second (negative) control group (Ravald and Birkhed 1992;Fure and Lingstrom 2009) or the results were presented according to different indices (DMFRS or texture) and did not report all information required for recalculation (Schaeken et al 1991;Tan et al 2010). For CHX mouth rinses (Powell et al 1999;Wyatt and MacEntee 2004;Wyatt et al 2007) and ozone treatment (Holmes 2003;Baysan and Lynch 2007), recalculation was not possible owing to insufficient data presentation. Thus, meta-analyses were performed only for dentifrice containing 5,000 ppm F -or 1.5% arginine plus 1,450 ppm F -, rinse containing 0.05% to 0.2% NaF (225 to 900 ppm F -), varnish containing SDF or CHX and combined use of dentifrice (1,500 ppm F -), and a rinse containing AmF/SnF 2 (250 ppm F -).…”
Section: Resultsmentioning
confidence: 99%
“…Regular rinsing with chlorhexidine did not have a substantial effect on the preservation of sound tooth structure in older adults. In a randomized clinical trial by Powell and others, 13 a weekly rinse with 0.12% chlorhexidine over three years did not reduce caries development significantly in a low-income older subjects population. This study was the only clinical study using 0.12% chlorhexidine rinse that was included in the review by Twetman.…”
Section: Mouthrinsesmentioning
confidence: 87%
“…Powell et al [1999] demonstrated a nonsignificant reduction of root caries events following weekly 0.12% CHX rinses and fluoride varnish compared with a group receiving 'usual' care from private practitioners. The other studies were 1-year placebo-controlled randomized trials, and one of them demonstrated a significant reduction and control of root caries lesions, suggesting regular antibacterial applications to be beneficial for these patient groups [Banting et al, 2000].…”
Section: Root Cariesmentioning
confidence: 83%
“…Three papers dealt with CHX treatments and root caries development in elderly and low-income older adults [Powell et al, 1999], dry-mouth risk patients [Banting et al, 2000] and in frail institutionalized people [Brailsford et al, 2002]. Powell et al [1999] demonstrated a nonsignificant reduction of root caries events following weekly 0.12% CHX rinses and fluoride varnish compared with a group receiving 'usual' care from private practitioners.…”
Section: Root Cariesmentioning
confidence: 99%
See 1 more Smart Citation